Introduction to Peptide Synthesis - Stawikowski, Maciej (2002)
A number of synthetic peptides are significant commercial or pharmaceutical products, ranging from the dipeptide sugar-substitute aspartame to clinically used hormones, such as oxytocin, adrenocorticotropic hormone, and calcitonin. This unit provides an overview of the field of synthetic peptides and proteins. It discusses selecting the solid support and common coupling reagents. Additional information is provided regarding common side reactions and synthesizing modified residues.